TLTC, a T5 exonuclease–mediated low-temperature DNA cloning method - Yu, Fang; Li, Xia; Wang, Fei; Liu, Yang; Zhai, Chao; Li, Wenqiang; Ma, Lixin; Chen, Wanping (Frontiers in Bioengineering and Biotechnology, 2023)
Molecular cloning is used in a wide variety of biological and medical research. Here, we developed a rapid and efficient DNA-assembling method for routine laboratory work. We discovered that the cleavage speed of T5 exonuclease is approximately 3 nt/min at 0°C and hence developed a T5 exonuclease–mediated low-temperature sequence- and ligation-independent cloning method (TLTC). Two homologous regions of 15 bp–25 bp compatible with the ends of the vector backbones were introduced into the inserts through PCR. Approximately 120 fmol of inserts and linear vectors was mixed at a molar ratio of approximately 3:1 and treated with 0.5 U of T5 exonuclease at 0°C for 5 min. Then, the mixture was transformed into Escherichia coli to generate recombinant plasmids. Single segment and multi-segments can be assembled efficiently using TLTC. For single segment, the overall cloning efficiency is above 95%. Moreover, extra nucleotides in the vectors can be removed during TLTC. In conclusion, an extremely simple and fast DNA cloning/assembling method was established in the present study. This method facilitates routine DNA cloning and synthesis of DNA fragments.